Mechanical and Morphological Characteristics Study of Chemically Treated Banana Fiber Reinforced Phenolic Resin Composite with Vajram Resin. Issue 12 (2nd December 2022) - Rajamanickam, Sathish Kumar; Manoharan, Mohanraj; Ganesan, S; Natarajan, P; Rajasekaran, P
ABSTRACT: The development of complete natural composite with natural fiber and natural resin is one of the challenges in the material era. To address the issue, this research article is aimed to study the possibility of utilizing the natural resin Vajram with natural banana fiber to develop a natural composite. In addition to that alkali treatment of banana fiber with 5%, 10% and 15% sodium hydroxide (NaOH) solution to improve the properties also analyzed. All the composites were prepared using a hand layup technique followed by compression molding. All the mechanical testings were conducted as per corresponding ASTM standards. The experimental results showed that 5% NaOH treated fibers recorded higher tensile strength 170.12 MPa than other fibers. Banana fiber reinforced phenolic resin composite (BFRPC) with 5% NaOH treated fibers with a 30% fiber weight ratio recorded the highest mechanical properties such as 22.62 MPa, 33.84 MPa, and 5.87 kJ/m 2 in tensile, flexural, and impact strength respectively. 21.53%, 38.39%, and 44.63% reduction in tensile, flexural, and impact strength respectively were noted due to the 80% Vajram mixed banana fiber-reinforced composite. This kind of low strength natural Vajram resin mixed banana fiber composites is well suitable for automobile applications as non-structural components.